2020
DOI: 10.1016/j.brs.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation: A novel approach in the treatment of vascular depression

Abstract: Background: Despite the impact of depression in terms of personal suffering and socioeconomic burden, most currently available treatment options are often ineffective. A particularly difficult-to-treat depressive disorder characteristic of the elderly is vascular depression, a late-life depressive syndrome related to a variety of potential vascular mechanisms. Transcranial Direct Current Stimulation (tDCS), a non-invasive and effective somatic approach to depression, also showed positive effects on cognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…The present results may also support the clinical interest of delivering two sessions of tDCS per day to achieve remission. This is in line with previous studies with comparable sample sizes, also reporting the beneficial effects of tDCS with two 30 min sessions per day, in a case-series of six patients with depressive disorders [9], six drug free patients with depression during pregnancy [20], and in a sample of 93 elderly participants [10]. The results are also consistent with studies reporting a beneficial effect of two 20 min sessions per day in 31 patients with depression (e.g., [21]), as well as in 30 patients with schizophrenia [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results may also support the clinical interest of delivering two sessions of tDCS per day to achieve remission. This is in line with previous studies with comparable sample sizes, also reporting the beneficial effects of tDCS with two 30 min sessions per day, in a case-series of six patients with depressive disorders [9], six drug free patients with depression during pregnancy [20], and in a sample of 93 elderly participants [10]. The results are also consistent with studies reporting a beneficial effect of two 20 min sessions per day in 31 patients with depression (e.g., [21]), as well as in 30 patients with schizophrenia [22].…”
Section: Discussionsupporting
confidence: 92%
“…Delivering 10 sessions with two 30 min sessions per day over 5 days [9] instead of delivering the more common protocol with one daily session delivered over 2 weeks, has numerous benefits for clinical settings and decreases the global cost of the intervention. Moreover, although there is no clear evidence in unipolar depression, it has been reported that delivering two daily sessions is a safe intervention and may induce better clinical benefits than the protocol with one single daily session, in patients with vascular depression [10].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the induced cortical lesion depends on the electrode pole: the anode depolarizes the cell membrane of neurons, thereby enhancing the activity of the neural cortex. On the other hand, cathodic stimulation causes hyperpolarization of the cell membrane of neurons, leading to a decrease in cortical excitation [103,111]. In the subacute phase of a stroke, increased activation of the contralateral hemisphere and hypoactivation of the damaged hemisphere are observed.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%
“…A recent study has indicated the effectiveness of tDCS in treatment-resistant vascular depression. 21 There are also reports of tDCS as a potential intervention for apathy, insomnia, alcohol dependence, etc. [22][23][24] Hence tDCS can be a potentially useful intervention for older adults with neuropsychiatric conditions.…”
Section: Role Of Transcranial Direct Current Stimulation (Tdcs) In Geriatric Mental Healthmentioning
confidence: 99%